Research progress on the effect of type 2 diabetes and hypoglycemic drugs on the prognosis of patients with colorectal cancer - ZHANG Meng，LEI Xuefen，CHEN Haixia，CHEN Yixuan，JIANG Li (Zhongguo linchuang yanjiu)
In recent years，the comorbidity of CRC and DM has become more and more common，and has become one of the public health problems that seriously endanger human health. The pathological mechanisms of DM such as hyperglycemia，insulin resistance and chronic inflammation can promote the progression of CRC.In addition，the effects of hypoglycemic drugs such as insulin，metformin，glucagon-like peptide-1 receptor agonist and SGLT2ion the prognosis of patients with T2DM complicated with CRC are also controversial. This article will comprehensively analyze the molecular mechanism of T2DM affecting the prognosis of CRC and the effects of different hypoglycemic drugs on the prognosis of CRC patients with T2DM.